2020
DOI: 10.5194/nhess-2020-43
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation of extreme rainfall and streamflow events in small Mediterranean watersheds with a one-way coupled atmospheric-hydrologic modelling system

Abstract: Abstract. Few studies evaluate the hydrologic performance of coupled atmospheric-hydrologic models when forced with observed rainfall and even fewer when forced with modelled precipitation. This information is crucial for the study of floods and in general for the use of the models for water management purposes. This study's objectives were: (i) to calibrate the one-way coupled WRF-hydro model for simulating extreme events in Cyprus with observed precipitation; and (ii) to evaluate the model performance when f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Arnault et al (2018) and Arnault, Wagner, et al (2016) brought evidence that a spinup period of a few months is sufficient to simulate realistic land surface conditions in Europe and West Africa with WRF-Hydro. In this study, the five-month spinup period is chosen as a compromise between the two-week spinup period employed for example in Camera et al (2020), and a one-year spinup period employed for example in Rummler et al (2019).…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Arnault et al (2018) and Arnault, Wagner, et al (2016) brought evidence that a spinup period of a few months is sufficient to simulate realistic land surface conditions in Europe and West Africa with WRF-Hydro. In this study, the five-month spinup period is chosen as a compromise between the two-week spinup period employed for example in Camera et al (2020), and a one-year spinup period employed for example in Rummler et al (2019).…”
Section: Model Setupmentioning
confidence: 99%
“…It is highlighted that the simulation of river discharge with WRF-Hydro-tag would require to activate an additional routing module in the river channels. Several studies have assessed the skill of WRF-Hydro in reproducing observed discharge (e.g., Camera et al, 2020;Fersch et al, 2020;Li et al, 2020;Senatore et al, 2020). In this study, the focus is on the contribution of lateral terrestrial water flow to the atmospheric branch of the hydrologic cycle, and no channel routing is considered.…”
Section: Model Setupmentioning
confidence: 99%
“…The Eastern Black Sea (EBS) and the Mediterranean (MED) regions of Turkey are among the most vulnerable regions in terms of flood risk in the Anatolian peninsula (Duzenli et al, 2020; Gurer, 1998; Gurer & Ucar, 2009). Forecasting the floods through high‐resolution NWP models in EBS and MED regions is critical (Camera et al, 2020), where a gradual increase in SST may cause sudden amplification of convective precipitation extremes over the coastal regions (Meredith et al, 2015) and SST variations play a key role in heavy precipitation events in the Anatolian Peninsula (Baltaci, 2017; Bozkurt & Sen, 2011; Turuncoglu, 2015). The SST forcing is usually considered as a crucial component for the heavy precipitation incidents, particularly over MED region (Robinson et al, 2012; Rebora et al, 2013; Senatore et al, 2014; Cisneros et al, 2016; Jee & Kim, 2017; Pastor et al, 2018; Furnari et al, 2018; Senatore, Furnari, et al (2020)).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the best prospects for predicting future behavior are using mathematical representations of the Earth's climate system through high-resolution regional climate and hydrological models that consider the peculiarities of the region. Although such applications are common in other parts of the world (Camera et al 2020 and references therein), there is a lack of relevant research studies that assess the performance of the hydro-climate models over the Nile and specifically over the EN basin. Few studies (Argent, 2014;Beyene et al 2010;Di Baldassarre et al 2011;Siam 2010;Weldemariam 2015) focused on the impacts of climate change on the hydrology at different regions in the Nile basin hydrology and Lake Victoria basin using dynamical and statistical downscaling techniques.…”
Section: Introductionmentioning
confidence: 99%